HYDROCORTISONE, ASCORBIC ACID, AND THIAMINE THERAPY DECREASE RENAL OXIDATIVE STRESS AND ACUTE KIDNEY INJURY IN MURINE SEPSIS. Issue 5 (4th November 2022) - Kim, John; Stolarski, Allan; Zhang, Qiuyang; Wee, Katherine; Remick, Daniel
ABSTRACT: Background : Acute kidney injury (AKI) occurs frequently in septic patients and correlates with increased mortality. Because clinical studies investigating hydrocortisone, ascorbic acid, and thiamine (HAT) have demonstrated discordant results, studies were performed using mortality stratification for therapy to identify candidates for therapy and determine mechanisms of organ injury. Methods : Sepsis was induced using the cecal ligation and puncture (CLP) model of sepsis with fluid and antibiotic support. Heart rate (HR) measurements obtained 6 hours after CLP stratified mice into live predicted (P-Live) or die predicted (P-Die). Stratified mice were then randomized for treatment with HAT or vehicle given 7 hours after CLP. Physiologic measurements were taken again at 24 hours, and mice were killed to collect blood and organs. Results : The following five groups were created: (1) P-Live vehicle, (2) P-Live HAT, (3) P-Die vehicle, (4) P-Die HAT, and (5) naive mice. Comparisons were made to test the hypotheses that (1) P-Die vehicle mice will have significant deterioration compared with P-Live mice targeting the kidney and (2) HAT will correct these deleterious changes in P-Die mice. Compared with P-Live, P-Die mice had a significant decline in all measured physiologic parameters (HR, cardiac output, breath rate, and temperature), which were corrected with HAT therapy ( P < 0.05 for all parameters). The P-Die mice had declines in the ascorbic acid within the blood, peritoneal lavage, and kidney homogenate compared with P-Live mice indicating consumption, and the decline was corrected with HAT. Elevated IL-6, KC, Macrophage Inflammatory Protein-2, and IL-1RA were found in P-Die mice and decreased with HAT. Markers of endothelial cell injury (glypican 1 and glypican 4) were elevated in the P-Die mice, and these values were decreased with HAT therapy. Low oxygen levels with subsequent oxidative stress (OS) in the kidney were visualized in histologic sections using hypoxyprobe and also with carbonyl proteins and 8-iso-prostaglandin F2α in kidney homogenates. The P-Die mice had significant elevations of renal OSs, which was ameliorated with HAT. Kidney injury was evident in the P-Die mice compared with P-Live mice with elevations in blood urea nitrogen and cystatin C, which were significantly reduced with HAT. There was no evidence of global hypoxia or organ injury because hepatic parameters remained normal. Conclusions: Our data show that in CLP-induced sepsis, P-Die mice have increased inflammation, OS, and kidney injury. Hydrocortisone, ascorbic acid, and thiamine therapy decreased renal OS and injury in the P-Die group when given after the onset of sepsis-induced physiologic changes.